Positional differences in jump loads and force and velocity metrics throughout a 16-week Division I volleyball season - Sanders, G. J.; Skodinski, S.; Cabarkapa, D. V.; Howard, M.; Cabarkapa, D.; Peacock, C. A. (Translational Sports Medicine, 2024)
The study quantified total and high-intensity jump counts and assessed neuromuscular performance through countermovement jump (CMJ) force and velocity metrics by position. Twelve Division I female athletes (19.6 ± 1.3 years; 182.7 ± 6.5 cm) were included in the 16-week study using wearable microsensors to monitor daily jump loads. CMJ tests were conducted twice weekly using dual force plates to measure force and velocity metrics. There were significant main effects of position (p = 0.001) for jump and force plate metrics. Middle blockers accumulated significantly more jump counts of 38.1 cm or higher (jumps 38+; 65.4 ± 39.2 counts) and jump counts of 50.8 cm or higher (jumps 50+; 39.5 ± 32.7 counts) compared to outside hitters (jumps 38+; 39.4 ± 25.9 counts and jumps 50+; 15.0 ± 15.6 counts) and opposite hitters (jumps 38+; 47.9 ± 24.1 counts and jumps 50+; 29.7 ± 18.1 counts), while setters had the fewest high-intensity jump counts (jumps 38+; 19.0 ± 16.6 counts and jumps 50+; 0.4 ± 0.8 counts). Middle blockers had the highest CMJ height (36.1 ± 6.4 cm), deepest CMJ depth (-41.7 ± 6.4 cm) and peak (2.75 ± 0.22 m/s) and average (1.49 ± 0.08 m/s) propulsion velocities (2.75 ± 0.22 m/s). Meanwhile, setters had significantly greater braking RFD (7839 ± 2617 N), average (1698 ± 223 N) and peak braking force (2061 ± 248 N), and average (1446 ± 88 N) and peak propulsion force (1994 ± 213 N), compared to all other positions. Opposite and outside hitters` data fell between setters and middle blockers. Regardless of position, neuromuscular performance fluctuates during the season and there are noticeable positional differences in jump loads and force and velocity metrics.